Impact of Indian Cinema on Youths Lifestyle and Behavior Patterns - Kethan M; Mahabub Basha S (East Asian Journal of Multidisciplinary Research, 2023)
The purpose of this paper is to document the impact of movies/cinema on Indian culture and to investigate the ongoing cultural transformations that have happened over a point of time in India owing to the contributions made by Indian cinema. Moreover, an attempt is made to understand how Indian movies have initiated various changes with regards to thought process on one hand and lifestyle on the other. There has been changes with regards to the institutions of marriage and instances of live in relationships have come of age and there has been a constant and continuous shift from joint families to nuclear families. Elaborating on the changes in the cultural practices; preferences have changed with regards to food habits, clothing, choice of career options and belief system. The distinctive contribution of the present paper is to offer an understanding of the impact of movies on Indian culture especially on the youth extracting information from the structured and in-depth interviews. This paper also tries to document the behavioral changes in the youth as a behavior patterns